Entre a docência e o ser docente: um olhar complexo - Barros, Tatiane Molini (2022)
English language teaching in Brazil has been losing its prestige over the years as today it only accounts for the minimum compulsory teaching hours of regular schools’ curriculum. This connotation directly impacts the practice of teachers, who, in the face of a more and more globalized international setting, understand the urgent need for English to be spoken and understood so that citizens can be part of a global world. Taking this context into account, I investigated, described and interpreted two phenomena of human experience –teaching and being a teacher – both, from the perspective of the English teacher. These phenomena have been experienced by nine participants, all of whom are English teachers that work in primary school, secondary school, high school, or as private teachers. This research is methodologically grounded on the Complex Hermeneutic-Phenomenological Approach (FREIRE, 2010, 2012, 2017), which, due to its qualitative nature, allows for objectivity and subjectivity to be systemically articulated throughout the interpretative process, thus helping finding out the essence of the human experience phenomena being studied. This research is theoretically grounded on the Epistemology of Complexity (MORIN, 1996, 2000, 2011a, 2011b, 2015a, 2015b), systemically articulated with the methodological approach chosen, and which has a transdisciplinary character, as understood by Moraes (2010) and Nicolescu (2000). This study was carried out by interpreting texts, electronically written by participants via Google docs due to Sars-CoV-2, answering three essay questions about the participants’ teaching journey and the reasons why they become teachers. The texts generated made it possible to carry out interpretation procedures, and to identify the themes that constitute the essence of the phenomena studied A close look at all themes identified seems to reveal the existence of a tension between both phenomena, and that investigating them from a complex perspective may be more inclusive, besides promoting relevant reflections upon. contemporary issues